Teaching EFL Speaking Using The Information Gap Technique - Isma Hendra (Universitas Syiah Kuala, 2018)
The aim of this study was: (1) to examine whether there could be a significant positive difference between the speaking achievements of students who are taught by using the Information Gap Technique and those who are taught through the traditional method, and (2) to explore the response of students to learning to use the Information Gap Technique in teaching-learning for EFL Speaking. This experimental study was conducted with second grade (year 11) students at SMAN 5 Takengon in the 2016/2017academic year. There were two classes taken for the sample: one as an experimental group (EG) and the other as the control group (CG). The sample classes were selected by using random sampling. The data was analyzed by using a T-test with SPSS processing for the speaking test and percentages for the questionnaire. The findings showed that the Information Gap Technique was more effective than the traditional method (teacher-centered) for teaching-learning speaking; this was proven by the results from the T-test, in which the findings showed that the T-test from the pre-test of the EG the CG was 1.3 (t count t table) which meant that there was no significant difference between the two scores from both classes. However, the post-test T-score for the EG the CG was 5.1 (t count t table) which indicated that there was a significant difference between the EG the CG post-test. Also the EG students had a very positive response (95%) to the use of the Information Gap Technique for their teaching-learning of EFL speaking. It can be concluded that the use of the Information-Gap Technique made a positive contribution for the development of the EFL speaking skills of the EG students.